Validación de un programa basado en las 3r par desarrollar actitudes ambientales, en los estudiantes del 5to grado de secundaria de la I.E Juan Velasco Alvarado - Pinto Balseca, Erison Luis (2014)
The present study aimed to implement an Environmental Program based on the 3Rs, to enhance the development of environmental attitudes in the fifth grade students of secondary schools in the lE Juan Velasco Alvarado Consuelo district, province of Bellavista. In this sense, attitudes were measured in their cognitive, affective and reactive components. According to the literature review the research hypothesis was formulated on the assumption that students develop their environmental attitudes if the program, the same one that consisted of experiential workshops, they were applied toa random sample of 25 students of the institution applies education. At the methodologicallevel, the type applied research was conducted under a preexperimental design, whose group of students were administered a pre and posttest to determine differences in the development of their attitudes. The test consisted of 25 questions, of which 1 o were from cognitive component, the affective component 5 and 1 O to the reactive component. Responses to the items were designed under a semantic scale and whose value ranged from 1 to 5 according to the importance of the answer. As for hypothesis testing for verification of the test corresponding to the t-student distribution with a confidence level of 95% was used paired difference, reaching demonstrated that the method based on the 3Rs Environmental Program students of School "Juan Velasco Alvarado" developed favorable environmental attitudes. Regarding the components of environmental attitudes in both the cognitive and affective component reagent, students also showed improvement in developing environmental attitudes, which was evident in the comparison of the results obtained in both the pretest and the posttest.